The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1272/jnms.82.170
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Ultrasound Assessment of the Displacement of the Median Nerve in the Carpal Tunnel during Wrist and Finger Motion in Healthy Volunteers

Abstract: Purpose: The purpose of this study was to investigate the displacement of the median nerve in the carpal tunnel during finger motion at varied wrist positions using transverse ultrasound in healthy volunteers, in order to clarify the appropriate position of a wrist splint in treating carpal tunnel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…3,6,7 In a previous study, we demonstrated the ultrasound technique to evaluate quantitatively the median nerve movement as a coordinate in the carpal tunnel during wrist and finger motion in healthy subjects and patients with CTS. 2,3 Subsequently, we found that at wrist palmar flexion position on the affected side, the median nerve moved statistically significantly the most ulnopalmarly among all wrist positions and became compressed the most strongly against the transverse carpal ligament by the flexor tendons in active finger flexion in patients with CTS. 3…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…3,6,7 In a previous study, we demonstrated the ultrasound technique to evaluate quantitatively the median nerve movement as a coordinate in the carpal tunnel during wrist and finger motion in healthy subjects and patients with CTS. 2,3 Subsequently, we found that at wrist palmar flexion position on the affected side, the median nerve moved statistically significantly the most ulnopalmarly among all wrist positions and became compressed the most strongly against the transverse carpal ligament by the flexor tendons in active finger flexion in patients with CTS. 3…”
Section: Discussionmentioning
confidence: 80%
“…The ultrasound image acquisition procedure has been described previously. 2,3 Briefly, each patient was seated with the elbow flexed, the forearm supinated, and the shoulder in neutral position. The forearm of the patient was fixed to a custom-made table with the wrist in the neutral position.…”
Section: Methodsmentioning
confidence: 99%
“…However, there has been little research detailing the transverse displacement of the median nerve within the carpal tunnel at various wrist positions during finger motion by ultrasound. We have recently described the ultrasound technique to evaluate quantitatively the median nerve movement as a coordinate within the carpal tunnel during wrist and finger motion in limited normal subjects (Nanno et al 2015). In the present study, using this technique, we evaluated the median nerve displacement within the carpal tunnel during wrist and finger motion in CTS patients.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, several studies reported that the median nerve moves longitudinally and transversely in response to active tendon motion in the carpal tunnel during finger or wrist movement (Nakamichi and Tachibana 1992;Erel et al 2003;Yoshii et al 2009;van Doesburg et al 2010). Additionally, some authors have used transverse ultrasound to evaluate median nerve motion in the carpal tunnel (Yoshii et al 2009(Yoshii et al , 2013van Doesburg et al 2010van Doesburg et al , 2012Wang et al 2014a, b;Nanno et al 2015). With use of this modality, it has previously been determined that the median nerve becomes displaced palmarly and gets compressed against the TCL in active finger flexion in healthy subjects and in patients with CTS (Yoshii et al 2009(Yoshii et al , 2013van Doesburg et al 2012;Wang et al 2014a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation